Hypertension as a Determining Factor in the Rupture of Intracranial Aneurysms, Diagnosed by 64-MDCT Angiography - Fatmawati, Heni; Santoso, Antonius G (UI Scholars Hub, 2017)
Background: To determine a correlation between risk factors and the rupture of intracranial aneurysms. Methods: A cross-sectional study of 29 patients with a saccular intracranial aneurysm was obtained using consecutive sampling and examination of 64-MDCT angiography. Bivariate statistical analysis using Fisher's exact test was arranged using cross-tabulation to determine the correlation between each risk factor of age, sex, hypertension, and smoking with the occurrence of ruptured intracranial aneurysms. Results: The highest incidence of ruptured intracranial aneurysms were in patients aged < 60 years (70%), male (75%), experienced hypertension (85%), and were smokers (85.7%). Only the risk factor of hypertension had a correlation with the occurrence of a ruptured intracranial aneurysm (p < 0.05). The prevalence ratio of age and sex were 1.0 and 0.9, whereas hypertension and smoking were 2.6 and 1.3. Conclusions: The risk factor of hypertension leading to a ruptured intracranial aneurysm was 2.6 times higher than non-hypertensive patients, and as such hypertension is a risk factor associated with the occurrence of ruptured intracranial aneurysms